2019
DOI: 10.5114/aoms.2018.74758
|View full text |Cite
|
Sign up to set email alerts
|

Association between neutrophil-to-lymphocyte ratio and parathyroid hormone in patients with primary hyperparathyroidism

Abstract: Introduction Primary hyperparathyroidism (PHPT) is associated with adverse cardiovascular outcomes which may result from an increase in systemic inflammation. Previously we have shown that serum parathyroid hormone (PTH) levels are independently associated with inflammatory indicators. The neutrophil-to-lymphocyte ratio (NLR) is an inexpensive, widely available marker of inflammation. In the present study, we aimed to assess the longitudinal changes in NLR before and after parathyroidectomy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
1
9
2
Order By: Relevance
“…Lam et al found a negative correlation between the serum phosphate and NLR values before PTX in patients with PHPT. Still, they also noted that this was not at a statistically significant level [18]. In our study, we detected a significant negative correlation between the serum phosphate and NLR values before PTX (r = 0.331, p = 0.046).…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Lam et al found a negative correlation between the serum phosphate and NLR values before PTX in patients with PHPT. Still, they also noted that this was not at a statistically significant level [18]. In our study, we detected a significant negative correlation between the serum phosphate and NLR values before PTX (r = 0.331, p = 0.046).…”
Section: Discussioncontrasting
confidence: 57%
“…They noted the regulatory effects of this procedure on systemic inflammation, which could also explain the beneficial role of PTX in anaemia, arterial stiffness, and survival in secondary hyperparathyroidism [ 23 ]. Lam et al detected a relationship between PHPT and systemic inflammation and found that systemic inflammation was reversible after rapid treatment [ 18 ]. Similarly, in our study, evaluating patients with PHPT, in the sixth month after successful PTX, there was a significant decrease was observed in NLR, which is an indicator of systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies confirmed these findings, one observing a positive correlation between serum NLR (but not PLR) and PTH levels in patients with hyperparathyroidism and identifying PTH as one of the main determinants of NLR, regardless the glomerular filtration rate, suggesting PTH as pro-inflammatory factor independent of renal dysfunction ( 88 ). The other study reported a correlation between preoperative NLR and both PTH and calcium levels in patients with primary hyperparathyroidism, with a significant 22% decrease in NLR after parathyroidectomy ( 87 ). Similarly, patients with secondary hyperparathyroidism had a significant decrease in NLR and PLR after successful parathyroidectomy, while those with persistent or recurrent disease had no changes, suggesting that effective parathyroidectomy may reduce systemic inflammation ( 86 ).…”
Section: Parathyroid Tumorsmentioning
confidence: 96%